Responsive Open Learning Environments Outcomes of Research from the ROLE Project - Kroop, Sylvana; Mikroyannidis, Alexander; Wolpers, Martin (Springer International Publishing : Imprint: Springer, 2015)
This book presents the outcomes of four years of educational research in the EU-supported project called ROLE (Responsive Online Learning Environments). ROLE technology is centered around the concept of self-regulated learning that creates responsible learners, who are capable of critical thinking and able to plan their own learning processes.  ROLE allows learners to independently search for appropriate learning resources and then reflect on their own learning process and progress. To accomplish this, ROLE´s main objective is to support the development of open personal learning environments (PLE's). ROLE provides a framework consisting of "enabler spaces" on the one hand and tools, content, and services on the other. Utilizing this framework, learners are invited to create their own controlled and preferred learning environments to trigger and motivate self-regulated learning. Authors of this book are researchers, developers and teachers who have worked in the ROLE project and belong to the ROLE partner consortium consisting of 16 internationally renowned research institutions, including those from 6 EU countries and China.  Chapters include numerous practical tutorials to guide the reader in creating innovative and useful learning widgets and present the best practices for the development of PLE's.